2009
DOI: 10.4161/epi.9021
|View full text |Cite
|
Sign up to set email alerts
|

Differential methylation persists at the mouseRasgrf1DMR in tissues displaying monoallelic and biallelic expression

Abstract: A subset of mammalian genes exhibits genomic imprinting, whereby one parental allele is preferentially expressed. Differential DNA methylation at imprinted loci serves both to mark the parental origin of the alleles and to regulate their expression. In mouse, the imprinted gene Rasgrf1 is associated with a paternally methylated imprinting control region which functions as an enhancer blocker in its unmethylated state. Because Rasgrf1 is imprinted in a tissue-specific manner, we investigated the methylation pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 45 publications
0
20
1
Order By: Relevance
“…We found that the Rasgrf1 gene was maternally expressed in the liver and small intestine, paternally expressed in the lung, and biallelically expressed in the brain, heart, spleen, kidney, stomach, pancreas, fat, testis, ovary, longissimus dorsi, and pituitary. These observations are not consistent with those from imprinting reports about the mouse and rat Rasgrf1 gene (Plass et al, 1996;Dockery et al, 2009;Drake et al, 2009). The differential imprinting status of the Rasgrf1 gene among rat, mouse and pig may be caused by the different species or the different tissues that were examined.…”
Section: Discussioncontrasting
confidence: 93%
See 2 more Smart Citations
“…We found that the Rasgrf1 gene was maternally expressed in the liver and small intestine, paternally expressed in the lung, and biallelically expressed in the brain, heart, spleen, kidney, stomach, pancreas, fat, testis, ovary, longissimus dorsi, and pituitary. These observations are not consistent with those from imprinting reports about the mouse and rat Rasgrf1 gene (Plass et al, 1996;Dockery et al, 2009;Drake et al, 2009). The differential imprinting status of the Rasgrf1 gene among rat, mouse and pig may be caused by the different species or the different tissues that were examined.…”
Section: Discussioncontrasting
confidence: 93%
“…Lane 1 = marker GM303 (the bands are 500, 400, 300, 200, 100, and 75 bp from top to bottom, respectively). neonatal brain, heart, stomach, and liver (Plass et al, 1996;Dockery et al, 2009). The imprinting of the mouse Rasgrf1 gene in a few tissues is relaxed during development, the transition from strongly and predominantly paternal allelic expression to biallelic expression can be seen over time, and expression becomes biallelic around the time of weaning (Drake et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Five imprinted genes have been identified on distal chromosome 9. Rasgrf1 is expressed in the placenta (Dockery et al 2009), but maternal UPD of the region is associated only with a post-natal growth restriction phenotype (Itier et al 1998, Clapcott et al 2003, Cattanach et al 2004.…”
Section: Imprinted Genes Not Associated With Upd Placental Phenotypesmentioning
confidence: 99%
“…Some genes are imprinted in all cell types, while others are imprinted in only a subset (Deltour et al 1995, Hu et al 1998, Yu et al 1998, Charalambous et al 2003, Dockery et al 2009). In particular, a number of genes imprinted in the placenta are not imprinted in the embryo (Hudson et al 2010, Okae et al 2012.…”
Section: Introductionmentioning
confidence: 99%